Railway Reform in South East Europe and Turkey : On the Right Track? - Monsalve, Carolina (World Bank, 2012)
The railways of South East Europe and Turkey experienced significant declines in traffic volumes in 2009. This reflected the impact of the international financial crisis unleashed in the last quarter of 2008 and its contractionary impact on the economies of the region and elsewhere. Lower traffic volumes translated in most cases into a serious deterioration of the financial performance of the state-owned railways. This brought home the costs of failing to implement essential reforms to improve the operational and financial performance of the sector when the economy was strong. In Romania in 2010, large-scale layoffs were announced at short notice for the state rail companies. The situation is similar for the Bulgarian state rail incumbents; they face an acute liquidity crisis, and will require additional state aid merely to keep running. The lesson of these events is clear: it is unwise to delay implementing state railway sector reforms during good economic times, because the consequences can be too severe if a financial downturn occurs before those reforms have been taken and properly implemented. This report begins by assessing implementation of the European Union (EU) legal and institutional framework and the state of institutional reform in South East Europe and Turkey. It then turns to a comparative assessment of the operational and financial performance of the rail sector in each of the 10 countries over 2005-2009, comparing the report countries with the EU-27 benchmark and three EU countries, Germany, Poland, and Slovenia. The report then moves on to the issue of rail corridor performance, with a specific focus on improving the institutional and regulatory environment at border-crossing points, before offering some conclusions. The first annex focuses on the performance of the incumbent state-owned railways of South East Europe and Turkey in much greater detail.